Strategi Pengelolaan Yayasan Az-Zahra (Rumah Kita) Griya Mangli Indah Jember dalam Mencapai Tujuan Dakwah - Ridlwan Hidayatullah; Ahidul Asror (Maddah: Journal of Advanced Da'wah Management Research, 2022)
Az-Zahra Foundation (Rumah Kita) is a religious social institution, as a forum for students or foster children to gain socio-religious knowledge located in Griya Mangli Indah Housing Jember. Research focus 1) What are the goals to be achieved in preaching? 2) What are the strategies used to achieve the goals of da'wah? 3) What are the supporting factors and inhibiting factors in delivering da'wah? This study uses a qualitative approach, data collection using interviews, observation, and documentation. Data analysis used descriptive qualitative. The results of the study are so that children do not drop out of school, get a proper education, both formal and religious, and get the love of their parents that they should get. The strategy to achieve the goal of preaching is by giving the name (Rumah Kita) so that students are free and not awkward in carrying out all activities at the Foundation because it is like their own home, providing proper formal education and non-formal education to students, providing tutoring facilities to students so that they can support their formal learning at school, provide teaching aids about religious activities, computer laboratory as a learning tool for millennial-era students, practice the knowledge they have acquired. Santri can apply it in daily life in the long term. Supporting and inhibiting factors are the established rules, methods, strategies, media and means to facilitate the delivery of da'wah. The inhibiting factors are the different personalities and backgrounds of students, the delivery of da'wah is not understood, the use of time is not conducive and students are naughty.